Intra-individual state-dependent comparison of plasma mitochondrial DNA copy number and IL-6 levels in patients with bipolar disorder - Kageyama, Yuki; Deguchi, Yasuhiko; Kasahara, Takaoki; Tani, Munehide; Kuroda, Kenji; Inoue, Koki; Kato, Tadafumi (Journal of affective disorders, 2022)
•We conducted two independent experiments using mouse model and human samples.•Neuron-specific mutant Polg1 transgenic mice revealed the presence of the brain-derived mitochondrial DNAs in the peripheral blood.•Plasma cell-free mitochondrial DNA (ccf-mtDNA) copy number, ND4/ND1 ratio, and IL-6 levels were measured in depressed and remitted states of the same bipolar disorder patients in a longitudinal manner.•Plasma ccf-mtDNA copy number, ND4/ND1 ratio, and IL-6 levels did not differ in depressed and remitted states of the same bipolar disorder patients.•Plasma ccf-mtDNA copy number nominally showed a positive correlation with delusional symptoms. Patients with bipolar disorder (BD) have increased plasma IL-6 levels, which are higher in depressed BD (dBD) than remitted BD (rBD). However, the mechanism that differentiates the cytokine levels between dBD and rBD is not understood. First, we determined whether brain-derived mtDNA can be detected in plasma using neuron-specific mutant Polg1 transgenic (Tg) mice. Second, we investigated whether the plasma circulating cell-free mitochondrial DNA (ccf-mtDNA) differentiate the cytokine levels between dBD and rBD. Mouse plasma ccf-mtDNA levels were measured using real-time PCR targeting two regions of the mtDNA (CO1 and d-loop) in Tg mice and non-Tg littermates. Human plasma ccf-mtDNA levels were measured using real-time PCR targeting two regions of the mtDNA (ND1 and ND4) and IL-6 levels were evaluated in 10 patients in different states (depressed and remitted) of BD in a longitudinal manner and 10 healthy controls. The mouse plasma CO1/D-loop ratio was significantly lower in Tg than non-Tg mice (P = 0.0029). Human plasma ccf-mtDNA copy number, ND4/ND1 ratio, and IL-6 levels were not significantly different between dBD and rBD. Human plasma ccf-mtDNA levels showed a nominal significant correlation with delusional symptoms (P = 0.033, ρ = 0.68). A larger sample size is required to generalize the results and to determine whether plasma ccf-mtDNA is associated with systemic inflammation. Tg mice revealed that brain-derived mtDNA could be present in peripheral blood. The present findings did not coincide with our hypothesis that plasma ccf-mtDNA differentiates the cytokine levels between dBD and rBD.